Some Elementary Properties of Neutrosophic Integers - Ayşe Nur Yurttakal; Yılmaz Çeven (Neutrosophic Sets and Systems, 2021)
: In this paper, we firstly defined a relation in the set of neutrosophic integers Z[I] and proved that this relation is an equivalence relation. Thus we obtained a partition of Z[I]. Secondly we investigated the ordering relation in Z[I] and we have seen that Z[I] is not a totally ordered set. We also gave some relations of positive and negative neutrosophic integers and ordering in Z[I] . In the last part of the paper, we introduced the factorial of a positive neutrosophic integer.